Investigating the relationship between work stress, job dedication, and personal well-being among childcare workers - Mahasookah Rahmaniah, Abdul Hashim (2025)
This study investigates the relationship between work stress, job dedication, and personal well-being among childcare workers in Kuantan, Pahang. Moreover, data were gathered from 54 participants employed in institution-based childcare centers through validated instruments: the Job Stress Scale, Well-Being Assessment, and a customized questionnaire for job dedication. Findings in the study reveals that 59.3% of participants reported moderate work stress levels, primarily influenced by high workloads, challenging child behaviours, and inadequate compensation. A smaller subset (5.7%) experienced high stress levels, correlating with lower job satisfaction and diminished well-being. Job dedication emerged as a mitigating factor, with 66.0% of participants identifying childcare as their chosen profession. A weak but statistically significant positive correlation (r = 0.299, p = 0.028) was observed between job views and motivations for pursuing childcare work, indicating alignment between personal values and professional roles. The study underscores the relationship of work stress on personal well-being, with participants reporting reduced mental and physical health, lower life satisfaction, and heightened anxiety. Despite these challenges, job dedication demonstrated a protective effect, enhancing resilience and caregiving quality. Addressing these findings, the study emphasizes the need for targeted interventions to manage stress, foster job dedication, and improve the overall well-being of childcare workers. Recommendations include introducing better workload management, competitive compensation, professional development opportunities, and supportive workplace environments to ensure sustainable and high-quality childcare services.